Chaos in Astronomy Conference 2007 - Contopoulos, G.; Patsis, P. A. (Astrophysics and Space Science Proceedings, 2009)
The conference "Chaos in Astronomy" was held in Athens on 17-20 Sep 2007. International leaders in the field addressed the topics Chaos in large N-body systems and in galactic dynamics Chaos in solar system dynamics Statistical mechanics of systems with regular and chaotic orbits Chaos in the formation of large-scale structure in the Universe Fundamental concepts, methods and tools. The book contains carefully edited refereed contributions. It serves as a reference to researchers and will give an overview to students and newcomers entering any field of dynamical astronomy.